2011
DOI: 10.1177/1465116511416680
|View full text |Cite
|
Sign up to set email alerts
|

Policy positioning in the European Parliament

Abstract: Party politics in the European Parliament consists of competition between transnational party groups, each consisting of multiple national member parties from the EU's 27 member states. Characterizing the policy space that these parties inhabit and their ideological positions is both practically and conceptually challenging. In this paper we characterize this policy competition by tracking EP political groups from three separate, original expert surveys taken in 2004, 2007, and 2010. We look at the relative po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 12 publications
2
65
1
5
Order By: Relevance
“…Hix et al 2007) and on ideological congruence (McElroy and Benoit 2010;2012). However, the similarity in our research findings was not a foregone conclusion.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Hix et al 2007) and on ideological congruence (McElroy and Benoit 2010;2012). However, the similarity in our research findings was not a foregone conclusion.…”
Section: Discussioncontrasting
confidence: 50%
“…McElroy and Benoit examine the ideological cohesion of national parties in EP party groups based on expert judgements of those parties' ideological positions (McElroy and Benoit 2010;2012). Thomassen and Schmitt (1999;see also Thomassen et al 2004) use data from surveys of MEPs to determine how cohesive and distinctive party groups are in relation to a set of broad policy questions.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-party cohesion, signalling consistency in voting behaviour among MEPs from the same ideological area, has been steadily increasing over time. Recent studies reinforce previous findings that EP party groups not only occupy the entire range of the left-right spectrum, but also are clearly distinguishable from one another in policy terms (McElroy and Benoit 2011). Furthermore, scholars showed that party groups, rather than nationality, have played a huge role in coalition formation in the EP from its very establishment (Kreppel and Tsebelis 1999;Kreppel 2000).…”
Section: Related Literaturesupporting
confidence: 71%
“…2 Furthermore, the distance between MEPs and their EPGs on each of the two dimensions is controlled for, and the position of the EPG is approximated by the mean of its members' positions. This procedure can be justified with reference to McElroy and Benoit (2012), who find that the position of all major EPGs is relatively close to the mean of the members. These distances are expected to be very powerful controls, because they address the individual MEPs' ideological motivation to deviate from their EPG.…”
Section: Scrutiny and Voting In The Epmentioning
confidence: 98%